Analysis of the rock dust effect on carbon storage and physicochemical soil variables in mangroves of Guayaquil, Ecuador - Veintimilla Gómez, Harry Enrique; Molina-Moreira, Natalia (Instituto de Ecología, A.C., 2023)
One way to reduce greenhouse gas emissions is to enhance Carbon (C) storage in mangrove sediment. However, environmental pollution hampers the optimal storage function of mangroves. A bio-stimulant named rock dust (RD) aids in remediating mangrove soil by adding nutrients. The effect of rock dust on C storage was analyzed vertically across the soil horizon in the Kennedy Norte Linear Park mangrove in Guayaquil. Four (25 m × 10 m) 250 m2 areas were established, with 1 kg of RD applied every 10 m2. To analyze the impact of RD on C storage, soil samples were collected at three different depths (0 m to 0.1 m / 0.2 m to 0.3 m / 0.4 m to 0.5 m) over 180 days, with sampling intervals of 30 days. A one-way ANOVA analysis was conducted on C in relation to depth, using the Tukey test at p < 0.05. Carbon (C), organic matter (OM), and nitrogen (N) percentages increased in depths 1 and 2 at 90 days after application and remained stable after that. No significant difference in C percentage between depths 1 and 2 was reported. The percentage increase can be attributed to the dry season and RD application. As for pH, it remained within a constant range of values near neutral. NH4 exhibited high ammonification rates. Similar behavior was observed in P and S due to contaminated effluent discharge and higher precipitation.